Investigations into the effects of mass transport and flow dynamics of spacer filled membrane modules using CFD - Saeed, Asim; Vuthaluru, Rupa; Vuthaluru, Hari (Elsevier, 2014)
Cross-flow membrane operations often experience material build-up on membrane surfaces leading to maintenance issues. Although several studies addressed the flow distributions and concentration patterns during membrane operations, the prediction of fouling propensities of top and bottom membranes are non-existent. Present study investigates the effects of dimensionless filament spacing of feed spacer on flow and concentration patterns on membrane surfaces. Comparisons of spacers in terms of a novel concept ‘Spacer Configuration Efficacy’, SCE (Sh/Pn)revealed that spacers with higher SCE values would lead to higher mass transport of the solute away from the membrane walls with moderate energy losses. Among the 16 spacer arrangements studied, spacer with filament spacing of 4 was found to be the optimal (Reh up to 200) with moderate pressure drop and higher values of mass transfer coefficient for the two membrane walls, further mass transfer coefficient values for the two membrane surfaces were found to be equal which leads to equal and lower fouling tendencies of the membrane walls.